2005
DOI: 10.1212/01.wnl.0000160116.65034.12
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation (K317M) in the MAPT gene causes FTDP and motor neuron disease

Abstract: Genetic analysis revealed the same novel mutation (K317M) in exon 11 of the MAPT gene in both pedigrees. A common haplotype between members of the two pedigrees suggests that they belong to the same family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 46 publications
3
80
0
1
Order By: Relevance
“…MAPT mutations have been associated with pure FTD [16] and with FTD with parkinsonism and/or MND [7, 9, 11, 17], but also with progressive sopranuclear paralysis and Alzheimer disease [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAPT mutations have been associated with pure FTD [16] and with FTD with parkinsonism and/or MND [7, 9, 11, 17], but also with progressive sopranuclear paralysis and Alzheimer disease [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Another association study by Fang et al [12] confirmed these findings and reported a higher incidence of breathing difficulties in sALS patients carrying specific MAPT genotypes. Moreover, in some studies, MAPT mutations have been reported to be associated with MND, although always in association with FTD [7, 9, 11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of astrocytic inclusions are generated in familial FTLD-tau linked to mutations in exons 1 and 10 and in introns following exons 9 and 10, the morphology of which largely depends on the MAPT mutation. Intracytoplasmic tau-immunoreactive inclusions in FTLD-tau are represented by tufted-like astrocytes, astrocytic plaques, ramified astrocytes, TSAs, astrocytes with globular inclusions and other types with no specific names [17,33,34,36,37,66,[77][78][79][80][81][82][83][84][85][86]. Tufted astrocytes and astrocytic plaques practically do not co-exist in PSP and CBD [57], but these lesions appear in combination in FTLD-tau [29] (Figure 4).…”
Section: Introductionmentioning
confidence: 99%
“…Additional, more detailed studies are needed to confirm whether mutations in TARDBP and FUS are indeed causative of "pure" FTD. Other genes associated with both ALS and FTD include MAPT, CHMP2B, DCTN1, ANG, DJ1, VCP, and PGRN (Annesi et al 2005;Munch et al 2005;Zarranz et al 2005;Mackenzie et al 2006;Parkinson et al 2006;van Es et al 2009a;Weihl et al 2009;Cox et al 2010;Johnson et al 2010). …”
Section: Genetic Correlation To Phenotype and Severity In Alsmentioning
confidence: 99%